Evaluation of Caterpillar C15 Diesel Engine Performance in Petroleum Applications Before and After Reconditioning Using Dynotest Testing - Muhamad Rajiv; Adrian Permana; Ali Ardin; Wanda Aprilia Savira; Fuad Zainuri; Muhamad Todaro (Jurnal Serambi Engineering, 2026)
This research aims to analyze the performance improvement of the Caterpillar C15 diesel engine based on dynotest data before and after the reconditioning process in petroleum applications. In field practice, low power conditions often become an issue that directly impacts unit productivity. The test results show that before the reconditioning, the engine could only produce a maximum power of 357 HP with a BMEP of 165.3 psi. After reconditioning, the performance significantly improved with power reaching 524 HP, an increase of approximately 46.8%. Additionally, the torque increased to 1313 lb·ft and the boost pressure reached 28 psi, followed by an increase in BMEP to 213.5 psi. This improvement indicates that the combustion process has become more efficient due to enhancements in the air and fuel supply systems. The performance curve shows a pattern that remains stable but shifts to a higher level, indicating an increase in efficiency without changing the basic characteristics of the engine. Thus, the reconditioning has proven effective in restoring engine performance and enhancing operational efficiency in petroleum applications.